2022
DOI: 10.4300/jgme-d-21-01144.1
|View full text |Cite
|
Sign up to set email alerts
|

Racial Bias on the Emergency Medicine Standardized Letter of Evaluation

Abstract: Background Studies on components of residency applications have shown evidence of racial bias. The Standardized Letter of Evaluation (SLOE) is an assessment measure for emergency medicine (EM) residency applications and, as more specialties opt to use SLOEs in place of narrative letters of recommendation, understanding bias on standardized assessments is essential. Objective To determine whether there is a difference in ranki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…The prior SLOE format had racial bias within multiple sections, including the GA: non-URM candidates were ranked statistically significantly higher than URM candidates. 2 Alvarez et al 3 had similar findings regarding the GA and also found disparities amongst the qualifications for EM questions. "Quiet" applicants were more likely to be placed in lower categories.…”
Section: O R R E S P O N D E N C E -R E S P O N S E T O L E T T E R S...mentioning
confidence: 82%
“…The prior SLOE format had racial bias within multiple sections, including the GA: non-URM candidates were ranked statistically significantly higher than URM candidates. 2 Alvarez et al 3 had similar findings regarding the GA and also found disparities amongst the qualifications for EM questions. "Quiet" applicants were more likely to be placed in lower categories.…”
Section: O R R E S P O N D E N C E -R E S P O N S E T O L E T T E R S...mentioning
confidence: 82%
“…In a hegemonically white educational context, black male and female students are discriminated against and less valued in terms of their intellectual potential than their white peers. This unequal treatment can be seen in the lower scores in admissions processes at American, English and Dutch universities and in letters of recommendation from American universities, as pointed out by Kukulski et al 39 and another study 40 . This discrimination can influence the low educational performance of some students, according to Loue et al 41 .…”
Section: Students and 143 Teachersmentioning
confidence: 91%
“…Kukulski P, et al 39 , 2022, USA, Quantitative Study II; I Identify differences in the classifications of black and white students.…”
Section: Students and 16 Residentsmentioning
confidence: 99%
“…Therefore, we must systematically identify and eliminate barriers to EM training for those who are underrepresented in medicine (URiM) and of historically marginalized identities. Racial bias has infiltrated traditional measures of excellence such as clerkship grading, medical student performance evaluation descriptors, honor societies, and the EM standardized letter of evaluation 15–18 . An overreliance on these biased measures to select trainees has contributed to the creation of a nonrepresentative workforce 19 .…”
mentioning
confidence: 99%
“…Racial bias has infiltrated traditional measures of excellence such as clerkship grading, medical student performance evaluation descriptors, honor societies, and the EM standardized letter of evaluation. [15][16][17][18] An overreliance on these biased measures to select trainees has contributed to the creation of a nonrepresentative workforce. 19 Holistic review has gained momentum as an evidence-supported method that more evenly balances the experiences, attributes, and metrics of residency applicants.…”
mentioning
confidence: 99%